Harm reduction drug policy in Israel: what has been accomplished and what still needs to be done? - Hagit Bonny-Noach (BMC, 2019)
Abstract The leading formal drug policy in Israel is the traditional approach of abstinence, probation, and punitive measures based on three main pillars: Enforcement, Treatment and Rehabilitation, and Prevention. However, under the treatment pillar, Israel has adopted a number of harm reduction services, focused mostly on people who use heroin and people who inject drugs. These include Methadone Maintenance Treatment, Buprenorphine Maintenance Treatment, and Needle and Syringe Exchange Programs. More specialized services are designated mostly for people who use drugs, who frequent the largest open drug scene in Tel-Aviv. These include a health clinic, an emergency apartment for female addict sex-workers, and a 'First Step' center. Even so, the harm reduction approach has remained controversial, stigmatized, and is considered a sub-category for total-abstinence treatment in Israel. This paper follows the evolution of harm reduction interventions in Israel among people who use drugs and sheds light on the lack of a comprehensive, well-planned, formal national harm reduction drug policy. Additionally, this article expresses concern over the uncertain future of Israel's comprehensive and balanced drug treatment policies caused by the structural changes in abolishing the Israel Anti-Drug Authority, the statutory authority and central body in Israel that promoted and coordinated all national policies related to treatment and harm reduction. Conclusions Although it is a major challenge to translate worldwide evidence and research findings into action and social change, recommendations are offered to implement a comprehensive harm reduction drug policy led by a multidisciplinary group of policy-makers across all areas of drug policy. These focus on expanding and developing more services for Opioid Maintenance Therapy patients and people who inject drugs as well as a national effort to reduce high levels of stigma and discrimination against them, encompassing other common substances and focusing on populations such as adolescents and young adults that engage in other types of substance use such as cannabis, amphetamine-type stimulants, and hallucinogens.